(untitled) (Bangladesh Journal of Botany, 2025)
The experiment was conducted to study the mean performance and heterosis for various traits in brinjal. Seven genotypes were crossed using a half diallel mating design, generating 21 hybrids that were evaluated along with parental lines and check variety (Kashi Taru). Analysis showed significant variability among genotypes and hybrids for studied traits. Superior parental genotypes based on performance were PPL, Arka Harshita and PPC. Promising hybrid combinations were PPL × Arka Harshita, PPC × LC-1, and LC-3 × Arka Harshita excelling in many traits. These hybrids show potential for wider testing and use in brinjal breeding programs. The findings underscore the value of hybrid development to advance brinjal cultivation and yield quality across diverse growing conditions. Bangladesh J. Bot. 54(3): 447-453, 2025 (September)